Decisions on the quality of piano performance: Evaluation of self and others - Morijiri, Yuki; Welch, Graham F. (Frontiers in Psychology, 2022)
In common with other professional musicians, self-evaluation of practice and performance is an integral part of a pianist’s professional life. They will also have opportunities to listen to and evaluate the performances of others based on their own criteria. These self-constructed perspectives toward to a piano performance will have an influence on both self-evaluation and external evaluation, but whether differently or similarly is not known. Consequently, this research study aimed to explore how judgements on the perceived quality of a performance are undertaken by professional standard pianists and what criteria are applied, both with regards their own performances as well as the performance of others. Participants were six professional pianists (3 men, 3 women) who were based in the UK (Mean age = 31.5 years old. SD = 5.1). They were asked to play individually six trials of a piece of R. Schumann’s “Träumerei” Op. 15 No. 7 in a hired hall for recordings. Then, within two months, each participant was asked to come to a self-evaluation session to listen to and evaluate their own six recordings, using a Triadic method as a Repertory Grid. For the external evaluation focused session, the participants were asked to return again to evaluate a further six recordings made up of ‘best’ recordings as selected by each participant from their own individual self-evaluations. Analyses of the resultant data suggest that there was no significant difference between the participants in their overall ratings in the external phase, but that self-evaluation showed significant individual differences amongst several participants. The performance criteria in both self-evaluation and external evaluation predominately overlapped with each other in terms of musical factors, such as tone quality, phrasing, and pedalling. The ranking of the performances was highly correlated with perceptions of overall flow, tone quality and pedalling. It appears that pianists apply similar criteria to decide performance quality when evaluating their own performances as well as others.